Stimuli-responsive polymer/nanomaterial hybrids for sensing applications. Issue 17 (3rd August 2020) - Shu, Tong; Shen, Qiming; Zhang, Xueji; Serpe, Michael J.
Abstract : Stimuli-responsive polymer (SRP)-based nanoparticles and SRP/nanomaterial hybrids have myriad applications, we review their uses for chemical sensing and biosensing. Abstract : Chemical and biological/biochemical sensors are capable of generating readout signals that are proportional to the concentration of specific analytes of interest. Signal sensitivity and limit of detection/quantitation can be enhanced through the use of polymers, nanomaterials, and their hybrids. Of particular interest are stimuli-responsive polymers and nanomaterials due to their ability to change their physical and/or chemical characteristics in response to their environment, and/or in the presence of molecular/biomolecular species of interest. Their individual use for sensing applications have many benefits, although this review focuses on the utility of stimuli-responsive polymer and nanomaterial hybrids. We discuss three main topics: stimuli-responsive nanogels, stimuli-responsive network polymers doped with nanomaterials, and nanoparticles modified with stimuli-responsive polymers.